The Moderating Role of Lifestyle on Insomnia in Home Quarantine College Students During the COVID-19 Epidemic - Zhang, Jinfang; Mi, Lin; Zhao, Jingbo; Chen, Huilin; Wang, Dongfang; Ma, Zijuan; Fan, Fang (Frontiers in Psychiatry, 2022)
There have been sufficient evidence for the relationship between lifestyle and individual insomnia, but for individuals already suffering from insomnia, it is not clear whether a good lifestyle can also be a beneficial factor. The present study investigated the role of different aspects of lifestyle in the development of individual insomnia by tracking the insomnia symptoms of college students during the COVID-19 lock-down. Two surveys were conducted on 65,200 college students in the process of home isolation in Guangdong Province, at the pandemic outbreak period (T1) and the initial remission period (T2), respectively. Given the objectives of the present study, a total of 1702 college students with clinical insomnia from T1 were selected as subjects. Insomnia symptoms were assessed using the Youth Self Rating Insomnia Scale (YSIS), and demographic information, epidemic exposure, and lifestyle were all measured by self-developed questionnaire, through network survey. The 1702 college students with insomnia symptoms were divided into three trajectory groups: recovery group, remission group, and chronic insomnia group according to their insomnia scores in T2 phase. The results showed that there was no significant difference in demographic backgrounds or epidemic exposure among the three groups, however, there were significant differences in food intake, exercise, and Internet use. The regression results further showed that both the recovery group and the remission group adopted more regular food intake than the chronic group. The recovery group exhibited better daily exercise habits than both the remission group and the chronic group. The duration of internet use was significantly shorter for the recovery group than for the chronic group. These findings indicated that, for college students with insomnia symptoms, who were isolated at home during the epidemic period, food intake routine, daily exercise habits and Internet use behaviors as part of their lifestyle will influence the development of insomnia symptoms, especially, the regularity of food intake may be a key factor contributing the natural recovery of insomnia.